The Effect of Collaborative Game-Based Outdoor Learning Model on Students' Learning Outcomes in Class VIII Social Studies - Shinta Oktafiana; Amalia Fauziya Rahmah (Antroposen: Journal of Social Studies and Humaniora, 2025)
The challenge in the current curriculum is that teachers are not only required to be able to master learning materials, but also to be able to apply learning models that are appropriate to the needs of students. One of the learning models that is considered fun and able to make students active in the learning process is by using a collaborative game-based outdoor learning model. The purpose of this study was to determine the effect of implementing a collaborative game-based outdoor learning model on student learning outcomes in class VIII of SMPN 6 Pamekasan. This study used a quantitative approach with the Quasi-Experimental method and the Pretest Posttest Nonequivalent Control Group Design . The results of the study found that the T-value of 2.216 with a significance level of 0.034 which is below 0.05 indicates that there is a real effect of the collaborative game-based outdoor learning model on student learning outcomes in Social Sciences (IPS) subjects. The significance figure of 0.034 which is smaller than 0.05 statistically proves that the research hypothesis is accepted. In addition, the experimental class with the Outdoor Learning model experienced an increase in learning outcomes of 57%, while the control class with the conventional model only achieved an increase of 26%.